The Effect of Generation Z Competencies and Work Culture on Employee Productivity at CV. Sinar Mojokerto - Totok Yulaidin; Nanang Andhiyan Mergining Mei; Ariani Alvi Anita; Octavia Refriyanti (PT FORMOSA CENDEKIA GLOBAL, 2026)
The use of this technology is also greatly influenced by the use of human resources in operating the technology. The ability of human resources or employees, both in terms of competence, creativity, and work discipline, greatly influences the development of the current printing business. In general, employees from the Gen Z generation have the ability to adapt more to digitalization, but have different characteristics from previous generations. Therefore, in this study, we raise this issue to clearly understand the factors that influence the development of the current printing business. In this study, we will examine the influence of Gen Z competencies and work culture on increasing work productivity at CV. Sinar Mojokerto. This study uses a quantitative method from questionnaire survey data related to competency and work culture variables, which were collected from several employees.